Understanding occupants' interaction with the technical change in low-carbon retrofits: a methodological and conceptual framework - Topouzi, M (European Council for an Energy Efficient Economy, 2011)
Little is known about the interrelations between behavioural aspects and physical dependences in energy use from empirical data. Empirical research on occupants’ ‘interaction’ with the technical changes in low-carbon retrofitted homes demands holistic socio-technical approaches. The aim of this paper is to present the methodological and conceptual framework of ongoing doctoral research focussed on the interaction between retrofitting interventions and occupants’ behaviour and the extent to which this affects the energy use of the UK’s refurbished housing stock. The paper discusses methods and occupant feedback techniques for low-carbon refurbishments. It presents the theoretical foundation of a methodological design developed to investigate, observe and analyse the ‘phenomena’ of individual household energy use based on one year’s monitoring data. The presented methodology is built up to estimate the ‘area of interaction’ of these variables on empirical findings, by defining the nature (direct/indirect, passive/active) and extent (low/zero, medium, maximum) of occupants’ interaction with technical refurbishment interventions. The paper concludes with an overview of a method structured to examine the importance of user’s ‘interaction’, by disaggregating the association of socio-technical variables and evaluating the behavioural dynamics in energy use.